Endovascular treatment with aortic endoprostheses for subclavian artery aneurysm secondary to late traumatic axillary-axillary arteriovenous fistula - Grillo, Vinicius Tadeu Ramos da Silva [UNESP]; Jaldin, Rodrigo Gibin [UNESP]; Rosa, Felipe Damascena [UNESP]; Secondo, Mariana Thais Silva [UNESP]; Pimenta, Rafael Elias Farres [UNESP]; Bertanha, Matheus [UNESP]; Sobreira, Marcone Lima [UNESP]; Yoshida, Winston Bonetti [UNESP] (FapUNIFESP (SciELO), 2021)
Traumatic arteriovenous fistulas (AVFs) involving the axillary and subclavian vessels are uncommon and account for 5 to 10% of all arterial traumas. The complex anatomy of this region makes treatment of this segment challenging. In this therapeutic challenge, we describe the case of a 73-year-old man, referred for progressive edema and ulceration involving the right upper limb and with a history of gunshot wound to the right infraclavicular region about 50 years previously. Angiotomography was performed and an axillary-axillary AVF was found, associated with tortuosity and aneurysmatic dilation of the subclavian artery downstream. He underwent endovascular intervention and a conical (monoiliac) 26 × 14 × 90 mm Braile® endoprosthesis was used in the aneurysmatic subclavian artery, posterior to the exit of the right vertebral artery and a 16 × 16 × 95mm Excluder® monoiliac endoprosthesis was placed overlapping the first prosthesis, showing a satisfactory result. Therefore, the possibility of successfully using aortic endoprostheses in an unusual and exceptional situation is described.
Tratamento endovascular com endoprótese aórtica para aneurisma de artéria subclávia secundário à fístula arteriovenosa axilo-axilar traumática tardia
Keywords: Arteriovenous fistula; Endovascular procedure; Subclavian artery; Vascular system injuries